A comparative case study of 2D, 3D and immersive-virtual-reality applications for healthcare education. (September 2020) - López Chávez, Omar; Rodríguez, Luis-Felipe; Gutierrez-Garcia, J. Octavio
Highlights: The design of a medical educational tool affects students' retention of information. Students' perception of gamification is that it improves learning on clinical cases. Immersive medical educational tools are preferred over tools with 2D/3D environments. Abstract: Background and objective: The workings of medical educational tools are implemented using a myriad of approaches ranging from presenting static content to immersing students in gamified virtual-reality environments. The objective of this paper is to explore whether and how different approaches for designing medical educational tools affect students' learning performance. Materials and methods: Four versions of an educational tool for the study of clinical cases were implemented: a 2D version, a gamified 2D version, a gamified 3D version, and a gamified immersive-virtual-reality version. All complying with the same functional requirements. Each version was used and evaluated by an independent group of students. The participants ( n  = 78) evaluated the applications regarding usefulness, usability, and gamification . Afterward, the students took an exam to assess the retention of information on the clinical cases presented. Results: One-sample Wilcoxon signed-rank tests confirmed that the participants perceived that it was at least quite likely that gamification helped improved their learning. In addition, based on the participants' perception, the gamification of the immersive-virtual-reality version helped the most to improve their learning performance in comparison with the gamified 2D and 3D versions. Conclusions: Regardless of whether different versions of a medical educational tool (complying with the same functional requirements) are perceived as equally useful and usable, the design approach (either 2D, 3D, or immersive-virtual-reality with or without gamification) affects students' retention of information on clinical cases.